2020
DOI: 10.1126/sciadv.aba5778
|View full text |Cite
|
Sign up to set email alerts
|

Methanol conversion on borocarbonitride catalysts: Identification and quantification of active sites

Abstract: Borocarbonitrides (BCNs) have emerged as highly selective catalysts for the oxidative dehydrogenation (ODH) reaction. However, there is a lack of in-depth understanding of the catalytic mechanism over BCN catalysts due to the complexity of the surface oxygen functional groups. Here, BCN nanotubes with multiple active sites are synthesized for oxygen-assisted methanol conversion reaction. The catalyst shows a notable activity improvement for methanol conversion (29%) with excellent selectivity to formaldehyde (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…This is because the codoped heteroatoms are not on the same aromatic ring structure, which significantly increases the conjugation effect and electronic delocalization of the graphitic carbon. [ 33 , 34 ] The increased negative charge of the C atoms around B and the reduced positive charge of P in the graphitic carbon of BPC may enhance π – π interactions between BA and BPC to facilitate the dissociation of H during BA oxidation. This also contributes to the formation of a more stable transition state (ts) and an optimal reaction pathway.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the codoped heteroatoms are not on the same aromatic ring structure, which significantly increases the conjugation effect and electronic delocalization of the graphitic carbon. [ 33 , 34 ] The increased negative charge of the C atoms around B and the reduced positive charge of P in the graphitic carbon of BPC may enhance π – π interactions between BA and BPC to facilitate the dissociation of H during BA oxidation. This also contributes to the formation of a more stable transition state (ts) and an optimal reaction pathway.…”
Section: Resultsmentioning
confidence: 99%
“…water) can activate methane 23 , 24 , introduction of secondary activators may be required to improve the product yield 25 . Oxidative dehydrogenation, selective oxidation, and the coupling ability of boron based catalysts such as borocarbonnitrides 26 28 and hexagonal boron nitride ( h -BN) 29 31 have been previously utilized in C1–C4 hydrocarbon to olefin conversion reactions. Although the C–H bond, molecular oxygen activation ability, and low carbon dioxide selectivity of B 2 O 3 has been studied 32 , using h -BN have not been exploited in methane to methanol conversion reactions under SC conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the catalytic activity of the BN material derived from the abundant edge sites in the oxidation state. The other key advantage of the BN catalyst was its outstanding oxidation resistance ability and very low CO 2 production in the aerobic oxidation process. Furthermore, Lu et al demonstrated that generating B-OH groups at BN edges upon steam activation could catalyze the conversion of propane to propylene, and the hydrogen abstraction of B-OH groups triggered propane dehydrogenation. ,, After that, Hermans et al updated their hypotheses and confirmed that the active phase consisted of three-coordinate boron sites with variable numbers of hydroxyl and bridging oxide groups under the ODHP reaction. , Wang and Huang et al also revealed and identified that the role of oxidative coupling of methyl was critical during the ODHP reaction, determined by the pathway of the gas-phase radical mechanism. , In view of these foundations, it is widely accepted that abundant BO X species are beneficial for the conversion of propane to propylene.…”
Section: Introductionmentioning
confidence: 99%